Sttudy off Facttorrs Associiatted wii tth Chii lldhood Nephrrott iic Syndrrome, Frrequentt Rellapsiing and IInff rrequentt Rellapsiing Type - Hanoudi, Basil M.; Mohammed, Rajaa; Al-Kaissi, Khalid Waleed (AL-Kindy College Medical Journal, 2014)
n each relapse. Objjec tt iiv es :: To sttudy diifffferentt ffacttors whiich miightt be associiatted or lleadiing tto tthe occurrence off rellapse iin nephrottiic syndrome Metthods:: A retrospective study of seventy patients with nephrotic syndrome with age range of 1-14 years, who were diagnosed and treated in Child’s Central Teaching Hospital over the period of 1st of January and 1st of July 2008. The patients were divided into three groups; frequent relapses group, infrequent relapses group and undetermined group. We compared between frequent relapses group and infrequent relapses group in regard to age, sex, type of presentation, biochemical findings which include; total serum protein, serum albumin and renal function test, precipitation factors, family history of renal disease, the time needed to respond to steroid therapy, duration of maintenance steroid therapy and type of renal biopsy. Res ull tts :: The peak incidence of nephrotic syndrome was at 1-5 years, and male to female ratio was 2.3:1. There was significant correlation of age and type of steroid response in nephrotic syndrome(P 0.042), and no significant correlation regarding sex(P 0.571). The relation of frequent relapsing and infrequent relapsing type with age and sex was not significant(P 0.864, 0.69 respectively), but hematuria had significant relation(P 0.036). Family history of nephrotic syndrome, early response to steroid therapy and the prolonged duration of maintenance steroid therapy were statistically significant in correlation with frequent relapses and infrequent relapses of nephrotic syndrome(P 0.05, 0.016, 0.024 respectively). There was significant difference in correlation of type of steroid response and type of relapse(P 0.001), and focal segmental glomerulosclerosis is prominent in frequent relapsing type(66.7%), while the minimal change type was prominent in infrequent relapsing nephrotic syndrome(40%). Conc llus iions :: There was significant correlation between family history of nephrotic syndrome, hematuria, response to steroid therapy, short duration of maintenance steroid therapy and type of steroid therapy response with occurrence of frequent relapses in nephrotic syndrome. There was increasing incidence of focal segmental glomerulosclerosis in frequent relapses.